A Systematic Review and Standardized Comparison of Available Evidence for Outcome Measures Used to Evaluate Proximal Humerus Fracture Patients. Issue 7 (July 2019) - Nowak, Lauren L.; Davis, Aileen M.; Mamdani, Muhammad; Beaton, Dorcas; Kennedy, Carol; Schemitsch, Emil H.
Abstract : Objectives: To summarize and appraise any patient-reported or clinician-measured outcome measures based on their measurement properties in proximal humerus fracture patients. Data Sources and Study Selection: MEDLINE, EMBASE, and CINAHL were searched from January 2000 to August 2018 to identify all studies of proximal humerus fracture patients that reported a measurement property evaluation of an outcome measure. Data Extraction and Synthesis: Quality appraisal of each measure was completed using the Evaluating the Measurement of Patient-Reported Outcomes (EMPRO) tool. The EMPRO takes into account all studies of each measure, and the overall score is transformed linearly to a range of 0 (lowest) to 100 (best). Results: Eleven instruments were identified. Intended concepts of the instruments included clinician-measured shoulder function, patient-reported function or disability, and patient-reported general health state. Only the Disabilities of the Arm, Shoulder and Hand (DASH), Oxford Shoulder Score, Constant Score, University of California, Los Angeles Shoulder Score, and EuroQol 5 Dimension (EQ5D) were evaluated in more than 1 study. The Shoulder Function Index (SFINX), DASH, and EQ5D had the highest EMPRO scores (80, 66, and 58, respectively). The SFINX and DASH consistently scored among the top 3 instruments for each attribute. Conclusions: Evidence on the measurement properties of outcome measures for proximal humerus fracture patients is limited. With the available evidence, the SFINX is recommended as a clinician-measured functional outcome measure, the DASH as a patient-reported functional outcome measure, and the EQ5D as a general health status measure. Abstract : Supplemental Digital Content is Available in the Text.